Alterations in the expression and activity of pre-mRNA splicing factors in hepatocarcinogenesis. (April 2014) - Berasain, Carmen; Elizalde, María; Urtasun, Raquel; Castillo, Josefa; García-Irigoyen, Oihane; Uriarte, Iker; Latasa, Maria U; Prieto, Jesús; Avila, Matías A
SUMMARY  Hepatocellular carcinoma (HCC) is a molecularly complex tumor that is resistant to standard and targeted therapies, and thus a deadly disease. In this context, the identification of key alterations driving HCC development is therefore essential. The implementation of next-generation sequencing techniques has underscored earlier realizations of the marked dysregulation of pre-mRNA splicing in HCC. Impairments in alternative splicing may lead to the expression of protumorigenic protein isoforms and to the generation of unstable mRNA species. Mechanistically, mutations in key nucleotides are responsible for many of these alterations in different types of tumors. However, changes in the expression of factors involved in the regulation of the splicing machinery are also important determinants in the derangement of pre-mRNA splicing. Here we discuss recent reports on the alteration of splicing factors in HCC, the pathological significance of these changes, and the identification of cell signaling pathways leading to the missplicing of genes in hepatocarcinogenesis.